Endothelial Cell–Specific Inactivation of TSPAN12 (Tetraspanin 12) Reveals Pathological Consequences of Barrier Defects in an Otherwise Intact Vasculature. Issue 11 (November 2018) - Zhang, Chi; Lai, Maria B.; Pedler, Michelle G.; Johnson, Verity; Adams, Ralf H.; Petrash, J. Mark; Chen, Zhe; Junge, Harald J.
Abstract : Objective—: Blood-CNS (central nervous system) barrier defects are implicated in retinopathies, neurodegenerative diseases, stroke, and epilepsy, yet, the pathological mechanisms downstream of barrier defects remain incompletely understood. Blood-retina barrier (BRB) formation and retinal angiogenesis require β-catenin signaling induced by the ligand norrin (NDP [Norrie disease protein]), the receptor FZD4 (frizzled 4), coreceptor LRP5 (low-density lipoprotein receptor-like protein 5), and the tetraspanin TSPAN12 (tetraspanin 12). Impaired NDP/FZD4 signaling causes familial exudative vitreoretinopathy, which may lead to blindness. This study seeked to define cell type-specific functions of TSPAN12 in the retina. Approach and Results—: A loxP-flanked Tspan12 allele was generated and recombined in endothelial cells using a tamoxifen-inducible Cdh5-CreERT2 driver. Resulting phenotypes were documented using confocal microscopy. RNA-Seq, histopathologic analysis, and electroretinogram were performed on retinas of aged mice. We show that TSPAN12 functions in endothelial cells to promote vascular morphogenesis and BRB formation in developing mice and BRB maintenance in adult mice. Early loss of TSPAN12 in endothelial cells causes lack of intraretinal capillaries and increased VE-cadherin (CDH5 [cadherin5 aka VE-cadherin]) expression, consistent with premature vascular quiescence. Late loss of TSPAN12 strongly impairs BRB maintenance without affecting vascular morphogenesis, pericyte coverage, or perfusion. Long-term BRB defects are associated with immunoglobulin extravasation, complement deposition, cystoid edema, and impaired b-wave in electroretinograms. RNA-sequencing reveals transcriptional responses to the perturbation of the BRB, including genes involved in vascular basement membrane alterations in diabetic retinopathy. Conclusions—: This study establishes mice with late endothelial cell–specific loss of Tspan12 as a model to study pathological consequences of BRB impairment in an otherwise intact vasculature. Abstract : Supplemental Digital Content is available in the text.